2013
DOI: 10.1039/c3dt51958a
|View full text |Cite
|
Sign up to set email alerts
|

A multiphase strategy for realizing green cathodoluminescence in 12CaO·7Al2O3–CaCeAl3O7:Ce3+,Tb3+ conductive phosphor

Abstract: A multiphase strategy is proposed and successfully applied to make the insulating green phosphor CaCeAl 3 O 7 :Tb 3+ conductive in the form of 12CaO·7Al 2 O 3 -CaCeAl 3 O 7 :Ce 3+ ,Tb 3+ . The phosphor shows bright green-light emission with a short lifetime (2.51 ms) under low-voltage electron beam excitation (3 kV). The green photo-and cathodoluminescence from 5 D 4 -7 F J ( J = 6, 5, 4, 3) transitions of Tb 3+ are significantly enhanced in comparison with pure C12A7:Tb 3+ . It was confirmed that this enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…found C12A7–Eu 2+ /Nd 3+ showed indigo long after‐glow with phosphorescence intensity increasing with doping content of Nd 3+ (0.05, 0.10 and 0.20 mol.%). Liu et al . found phosphor of C12A7–Tb 3+ /Ce 3+ (with additional phase of CaCeAl 3 O 7 ) with green light emission of short lifetime (2.51 ms) under low‐voltage electron beam excitation (3 kV).…”
Section: Derivatives Of C12a7mentioning
confidence: 99%
See 4 more Smart Citations
“…found C12A7–Eu 2+ /Nd 3+ showed indigo long after‐glow with phosphorescence intensity increasing with doping content of Nd 3+ (0.05, 0.10 and 0.20 mol.%). Liu et al . found phosphor of C12A7–Tb 3+ /Ce 3+ (with additional phase of CaCeAl 3 O 7 ) with green light emission of short lifetime (2.51 ms) under low‐voltage electron beam excitation (3 kV).…”
Section: Derivatives Of C12a7mentioning
confidence: 99%
“…For C12A7-Er 3+ and C12A7-Yb 3+ /Er 3+ , two main emission bands centered around 530/550 nm [green, up-conversion emission intensity increasing with doping content of Er 3+ (1.0, 1.5, 3.0 mol.%)] and 660 nm [red, with intensity ratio of red-to-green up-conversion emission increasing with doping content of Yb 3+ (1.0, 2.0, 10.0 mol.%)/Er 3+ (fixed at 1.0 mol.%)] were observed via up-conversion process by Wang et al 22 Zhang et al 77 found C12A7-Eu 2+ /Nd 3+ showed indigo long after-glow with phosphorescence intensity increasing with doping content of Nd 3+ (0.05, 0.10 and 0.20 mol.%). Liu et al 25 found phosphor of C12A7-Tb 3+ /Ce 3+ (with additional phase of CaCeAl 3 O 7 ) with green light emission of short lifetime (2.51 ms) under low-voltage electron beam excitation (3 kV). Liu et al 27 found optical performances of C12A7-Re derivatives were affected by the sort and amount of encaged anions via optical and EPR spectroscopy analysis.…”
Section: Derivatives Of C12a7mentioning
confidence: 99%
See 3 more Smart Citations